Application of egg powder in diets and its effect on serum parameters of juvenile rainbow trout - Keleştemur, Gülüzar Tuna; Keleştemur, Neslihan; Uslu, Ali Atilla (My University, 2022)
In our study, the effect of dietary supplemented with 16.5%, 27.5%,% 38.5%, 63.2% (respectively diet group; Y1, Y2, Y3, Y4) egg powder instead of fish meal on blood (ions, lipids, proteins) parameters of rainbow trout were determined. Fish were fed with different diets containing egg powder, and control diet (without supplemented) for 12 weeks. The Oneway ANOVA test results showed that serum lipids, protein and ions levels were affected by dietary supplementation egg powder. Serum glucose level was significantly decreased in Y4 group (p<0.05). Serum TP level was not statistically different among research groups (p>0.05). Serum creatinine level was significantly increased Y3 and Y4 (p>0.05) diet groups. Serum uric acid, BUN and urea levels were increased in Y1,Y2, Y3, Y4 diet groups compared to control groups (p<0.05). The highest Mg levels were determined in Y3 group (p<0.05). Besides, Mg and P levels were decreased in particular control and Y4 groups (p<0.05) according to other diet groups. However, it is concluded that the value of lipid in blood showed an increasing tendency with the increasing percent in diet egg powder.
Keywords: Serum parameters; Rainbow trout; diet; egg powder; animal protein source